Sustainable water - Ainger, C. M.; Fenner, Richard (Delivering sustainable infrastructure., 2016)
'Sustainable Water' is a practical and accessible resource for engineers and other professionals who play vital roles in creating and maintaining water services. As part of the 'Delivering Sustainable Infrastructure' series, the work follows a framework of fundamental sustainability principles and offers guidance and examples of how these can be applied to the water sector. It is designed to be readily accessible to practitioners and contains contributions from many leading voices in the water industry.